Influence of Adding cRGD Peptide to Phospholipide Nanoparticles with Doxorubicin Included on Apoptosis in Glioblastoma Cells in Vitro - Kostryukova, L.V.; Tereshkina, Yu.A.; Gisina, A.M.; Bedretdinov, F.N.; Pyatigorsky, A.M. (Biomedical Chemistry: Research and Methods, 2023)
One of the methods of treating glioblastoma after surgery is chemotherapy; the drugs used in this case, due to their nonspecific distribution, lead to a number of complications. One way to overcome this drawback is to supply drugs with delivery systems with targeted molecules. This approach allows increasing the accumulation of therapeutic agents directly at the lesion site, minimizing side effects. This work is a continuation of the study of the mechanism of action of the previously obtained phospholipid composition of doxorubicin with a targeted cRGD peptide (NPh-Dox-cRGD). This peptide is capable of selectively interacting with integrin αvβ3, a receptor expressed on the surface of a number of tumor cells, including glioblastoma. The work assessed the cytotoxic effect of the NPh-Dox-cRGD composition in comparison with the free substance (Dox) and embedded in phospholipid nanoparticles without a targeted ligand (NPh-Dox). It was shown that after 24 h of incubation of U-87 MG cells with substances at the maximum concentration of Dox (30 μg/ml), the percentage of viability cells was 6% for Dox, 21% for NPh-Dox-cRGD, and 21% for NPh-Dox – 17%, i.e. When Dox was incorporated into phospholipid NPs, its cytotoxic effect was observed to a lesser extent. No statistically significant differences were noted in the control line HeLa. Assessment of tumor cell death using flow cytometry indicated that most of the cells died via apoptosis. When incubated with a composition containing a targeting peptide, NPh-Dox-cRGD, at a concentration (Dox) of 0.5 μg/ml, the percentage of cells susceptible to late apoptosis was 29.7%, for the free form – 24.4%. An assessment of cells susceptible to early apoptosis (Dox concentration 0.5 μg/ml) showed that the percentage of these cells for the sample with the peptide was higher and amounted to 11.4%.